The dialogues conversations about the nature of the universe - Clifford V. Johnson (London, England : The Mit Press, 2017)
"In this graphic book/novel, readers eavesdrop on conversations about contemporary science and learn about how scientists uncover the secrets of the universe. Topics in the book range from black holes, to the multiverse, to string theory, to food science. The book is structured as a set of 9 conversations in 11 chapters. The people in the conversations include non-experts and experts in physics, both adults and children, both male and female. These characters are fictional. The locations are in cities around the world, in cafes, train stations, on the street, buses, museums, libraries. The book is, uniquely for this subject matter, a fully graphic book. A graphic novel, but NOT science fiction. The science is real, and often concerns research topics that have been highlighted in general-interest media outlets"-- Provided by publisher.
Keywords: Science